1988
DOI: 10.1111/j.1399-3011.1988.tb00900.x
|View full text |Cite
|
Sign up to set email alerts
|

Further studies on the resolution of human mercapt‐ and nonmercaptalbumin and on human serum albumin in the elderly by high‐performance liquid chromatography

Abstract: High‐performance liquid chromatographic (HPLC) analysis of human serum albumin (HSA) on Asahipak GS‐520 showed at least two peaks, the principal component corresponding to human mercaptalbumin (HMA) and the secondary one to nonmercaptalbumin (HNA). HPLC analysis of HSA on Asahipak ES‐520 N showed three peaks, the principal component corresponding to HMA, the secondary one to HNA having mixed disulfide with cysteine or glutathione and the tertiary one to HNA oxidized higher than mixed disulfide. Two kinds of ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 16 publications
1
48
0
Order By: Relevance
“…The fraction of oxidized albumin is also increased in diabetes mellitus (53), disorders of the temporomandibular joint (54), senile cataract (55), and invasive surgery (56). Furthermore, it has been shown that the fraction of oxidized albumin also increases with aging (26,35) and intense exercise (57).…”
Section: Implications In Pathologymentioning
confidence: 95%
See 1 more Smart Citation
“…The fraction of oxidized albumin is also increased in diabetes mellitus (53), disorders of the temporomandibular joint (54), senile cataract (55), and invasive surgery (56). Furthermore, it has been shown that the fraction of oxidized albumin also increases with aging (26,35) and intense exercise (57).…”
Section: Implications In Pathologymentioning
confidence: 95%
“…The heterogeneity of albumin can be revealed, among other techniques, by anion exchange-hydrophobic interaction chromatography (26) and mass spectrometry (27,28). The fraction containing the reduced thiol is known as mercaptalbumin and comprises ~7 0% of total albumin, whereas the nonmercaptalbumin fraction consists mainly of mixed disulfides between Cys34 and low molecular weight thiols, mostly cysteine (25%) (27).…”
Section: Heterogeneity Of the Albumin Thiolmentioning
confidence: 99%
“…The Cys-34 of HSA makes up approximately 80% of the total free thiol content in plasma [15] and the state of Cys-34, i.e., the redox state of HSA, is thus indicative of the degree of short-term systemic oxidative stress because of the short half-life (*20 days) of the albumin molecule [15]. We have developed a convenient high-performance liquid chromatography (HPLC) system for the clear separation of HSA into HMA and HNA [16,17], and we have extensively studied the dynamic changes of HSA(Cys-34)-redox state under various physiologic [18][19][20] and pathophysiologic states, such as hepatic [21,22], renal [5,[23][24][25][26], diabetic [27], and other diseases [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…We have developed a convenient HPLC method for separation of HSA into HMA and HNA [5,6] and have extensively studied the dynamic changes of the HSA-thiol redox state under various physiologic [7][8][9][10] and pathophysiologic states, for example hepatic [11,12], renal [13][14][15][16][17][18], diabetic [19,20], and other diseases [21][22][23].…”
Section: Introductionmentioning
confidence: 99%